2021
DOI: 10.3390/f12101418
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity and Ecosystem Functioning in Deadwood of Black Pine of a Temperate Forest

Abstract: The present study provides a deeper insight on variations of microbial abundance and community composition concerning specific environmental parameters related to deadwood decay, focusing on a mesocosm experiment conducted with deadwood samples from black pine of different decay classes. The chemical properties and microbial communities of deadwood changed over time. The total carbon percentage remained constant in the first stage of decomposition, showing a significant increase in the last decay class. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
3
6
0
Order By: Relevance
“…In our study, the total nitrogen content of deadwood gradually increased from decay classes I–V, consistent with the results of Pastorelli et al. ( 2021 ), which might be due to the effect of nitrogen‐fixing bacteria and the transport of some ectomycorrhiza or some fungi. The total organic carbon content gradually decreased from decay classes I–V, consistent with the study of Yang et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the total nitrogen content of deadwood gradually increased from decay classes I–V, consistent with the results of Pastorelli et al. ( 2021 ), which might be due to the effect of nitrogen‐fixing bacteria and the transport of some ectomycorrhiza or some fungi. The total organic carbon content gradually decreased from decay classes I–V, consistent with the study of Yang et al.…”
Section: Discussionsupporting
confidence: 93%
“…A large number of studies have shown that some nitrogen-fixing bacteria, ectomycorrhiza or some fungi can affect the N content in deadwood (Bentzon-Tilia et al, 2015;Rinne et al, 2016). In our study, the total nitrogen content of deadwood gradually increased from decay classes I-V, consistent with the results of Pastorelli et al (2021), which might be due to the effect of nitrogen-fixing bacteria and the transport of some ectomycorrhiza or some fungi. The total organic carbon content gradually decreased from decay classes I-V, consistent with the study of Yang et al (2021), which may be attributed to the decomposer reducing the carbon content in the deadwood through respiration.…”
Section: Driving Factors Of Microbial Community Changes In P Massonia...supporting
confidence: 89%
“…In addition, they have also evolved a prominent capability of efficiently depolymerizing and mineralizing lignin, which is the most recalcitrant component in PCW (Martínez et al, 2005;Fernandez-Fueyo et al, 2012;Floudas et al, 2012). The degradation of lignin and polysaccharides by white-rot fungi mainly relies on the activity of oxidoreductases and glycoside hydrolases, respectively (Sánchez, 2009;Floudas et al, 2012;Qin et al, 2018;Pastorelli et al, 2020). The white-rot fungus Lentinula edodes, also called as Xianggu in China or shiitake in Japan, produces a large suit of extracellular enzymes to degrade cellulose, hemicellulose, and lignin (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, declining microbial species richness in response to habitat loss resulted in decreased microbial activity and thus decreased rates of deadwood decomposition (Tomao et al., 2020; Young et al., 2005). In turn, CO 2 emission rates were shown to be directly correlated with fungal and bacterial richness (Pastorelli et al., 2021), which are influenced by different management strategies. The factors that govern respiration processes from deadwood decomposition are not fully understood and the majority of existing studies focus on forest environments with closed canopies or old‐growth forests with high levels of deadwood (Harmon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%